1970
DOI: 10.1017/s0022216x00005095
|View full text |Cite
|
Sign up to set email alerts
|

The Empire Builders: A History of the Bolivian Rubber Boom and the Rise of the House of Suárez

Abstract: Fascination with the history of the South American rubber boom never wanes. Its innate dramatic quality, the extraordinary touches of the bizarre which spice its narrative, and the ironic blend of climax and catastrophe which distinguish almost every aspect of its development have all proved sufficient guarantee against oblivion. Drawn by the curiosity of circumstances such as these, travellers have since penetrated the region to see for themselves the remains of former prosperity, and to marvel upon the stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 21 publications
0
15
0
5
Order By: Relevance
“…As mentioned, the foundation of the Brazil nut economy emerged in the second half of the nineteenth century as early entrepreneurs moved across the Amazon to establish large forest estates to extract rubber (referred to as seringais in Portuguese and barracas or fundos in Spanish ;Fifer 1970;Weinstein 1983;Coomes and Barham 1994). From the colonial period, estate owners in the Amazon had depended on coerced labor from indigenous people, but as the rubber boom accelerated, labor shortages required that they bring indentured workers from outside the region to settle in forests and extract rubber latex for global markets.…”
Section: The Resource Usersmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, the foundation of the Brazil nut economy emerged in the second half of the nineteenth century as early entrepreneurs moved across the Amazon to establish large forest estates to extract rubber (referred to as seringais in Portuguese and barracas or fundos in Spanish ;Fifer 1970;Weinstein 1983;Coomes and Barham 1994). From the colonial period, estate owners in the Amazon had depended on coerced labor from indigenous people, but as the rubber boom accelerated, labor shortages required that they bring indentured workers from outside the region to settle in forests and extract rubber latex for global markets.…”
Section: The Resource Usersmentioning
confidence: 99%
“…For such cases, substantial numbers of families continue to supply migrant labor (especially in Bolivia). Although machinery to shell Brazil nuts was brought to the Amazon in the early twentieth century (Fifer 1970), it was not until the 1990s that processing plants became more prominent, particularly in Bolivia ( Fig. 2d; Cronkleton and Pacheco 2010).…”
Section: Supply Chains Cooperatives and Certificationmentioning
confidence: 99%
“…The state was largely absent from lowland Bolivia from the colonial period until the mid-1950s. The most important event during the late 19th century was the occupation of the upper Amazon stimulated by a growing international market for rubber that fostered large-scale land estates claimed by a handful of investors [43]. This occupation faced strong local resistance from indigenous populations whose lands were confiscated and who ended up working in the rubber estates [44].…”
Section: State Policy and Land Appropriation In Lowland Boliviamentioning
confidence: 99%
“…A Parliamentary commission found that one firm operating in Peru had resorted to mutilation, torture, and murder to coerce the local population into rubber production (Weinstein, 1983, p. 26). Bolivian rubber production took off after Heath's exploration of the Beni river in 1880; by 1890 the country's rubber production was so concentrated in the house of Suárez that contemporaries referred to his organization as an 'empire' (Fifer, 1970).…”
Section: Background and Sourcesmentioning
confidence: 99%